Spatial Modelling for Regency & City Covid-19 Alertness Index After Eid Holiday in Central Java Province - Rezky Yayang Yakhamid (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2021)
The Covid-19 pandemic has spread throughout the world, including Indonesia. The increase in Covid-19 cases in Indonesia is influenced by long holidays. Eid holidays accompanied by violations of going home and also health protocols are suspected of causing the spread of Covid-19 after Eid. This study aims to determine the factors that significantly affect the Regency/City Covid-19 Alertness Index (IKK) in Central Java Province after the Eid holiday. The data analysis method used is spatial analysis using spatial regression. The results showed that the spatial error regression (SEM) was better than the other models. The regional classification variables, the percentage of doctors per 10,000 population, and the percentage of the poor, and the open unemployment rate have a significant effect on the IKK.